PENGEMBANGAN SDM DALAM PEMBANGUNAN EKONOMI - Darto, Mariman (Jurnal Bestari, 1993)
To build physical needs usually will be easier than to build human resources. The state of development in very country will be identified by the state of their human resources. It is, therefore, important to develop human resources to be skilfull in many fields. When economic affairs are considered as the strategic basic of national development program, building human resources must be understood as the most strategic conditions to get the ideals of every nation.